Real‐world opportunity of empagliflozin to improve blood pressure control in African American patients with type 2 diabetes: A National Cardiovascular Data Registry "research‐to‐practice" project from the diabetes collaborative registry. Issue 2 (25th September 2018) - Arnold, Suzanne V.; Seman, Leo; Tang, Fengming; Peri‐okonny, Poghni A.; Ferdinand, Keith C.; Mehta, Sanjeev N.; Goyal, Abhinav; Sperling, Laurence S.; Kosiborod, Mikhail
Abstract : The 1245.29 Trial recently showed that empaglifozin improved both blood pressure and glucose control in African American (AA) patients with type 2 diabetes (T2D) and hypertension. Using the Diabetes Collaborative Registry, a large‐scale US registry of outpatients with diabetes recruited from primary care, cardiology and endocrinology practices, we sought to understand the potential impact of these observations in routine clinical practice. Among 74 290 AA patients with T2D from 368 US clinics, 60.4% had hypertension, of whom 34.5% had systolic blood pressure ≥ 140 mm Hg (20.8% of the total AA T2D population). Only 1.7% of this eligible population had been prescribed a sodium‐glucose co‐transporter two inhibitor. The mean estimated 5‐year risk of cardiovascular death was 7.7%, which could be reduced to 6.2% when modelling the antihypertensive effect of empagliflozin across the eligible population (based on an 8‐mm Hg blood pressure reduction). These findings may represent a potential opportunity for better management of cardiovascular risk factors and improved outcomes in this vulnerable cohort.